Recombinant Revelations: 2012 in Millenarian and New Age Cyber-Apocalypticism: Discourse Analysis of Symbolism and Visual Rhetoric in two Digital Environments Predicting the 2012 Apocalypse - Hubbes, László Attila (Traditiones, 2022)
This article investigates apocalyptic spirituality in the contemporary globalized context of re-emerging religiousness and New Age spirituality, in which millennial calendrical anxieties, a conspiracy mentality, and crisis consciousness are bolstered up by the visual flood of old and new electronic media. Two types of religious or spiritual digital environments are presented through their characteristic imagery: the rather traditional environment of Christian millennialism and the hyper-eclectic atmosphere of New Age networks.